Assessing injury risk in Indonesian pickleball athletes using the Functional Movement Screen (FMS) - Dinan Mitsalina; Sandi Prayudho; Apta Mylsidayu (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
Pickleball has experienced rapid growth in participation; however, this trend has been accompanied by an increasing incidence of musculoskeletal injuries. This study aimed to assess injury risk among Indonesian pickleball athletes using the Functional Movement Screen (FMS) and to examine its potential as a predictive tool for injury prevention. A quantitative prospective cohort design was employed, involving 35 athletes (30 amateurs and 5 professionals) monitored over a 12-month competitive season. Baseline FMS assessments were administered by certified raters, and injuries were recorded weekly. Injury was defined as any condition resulting in at least one day of absence from training or competition. The results showed that professional players demonstrated significantly higher FMS scores (mean = 16.0) compared to amateur players (mean = 12.3). During the season, 18 injuries were documented, predominantly knee and ankle injuries among amateurs and shoulder injuries among professionals. Logistic regression analysis indicated that lower FMS scores were significantly associated with a higher risk of injury, with each one-point decrease in FMS score increasing injury risk by 2.85 times (OR = 2.85; 95% CI = X–X; p < 0.05). These findings suggest that FMS is an effective screening and predictive tool for analyze injury risk in pickleball athletes and can support the development of targeted preventive training programs, particularly for amateur players. Notably, this study contributes novel evidence to the limited body of research examining injury risk profiling in pickleball athletes using validated movement screening tools, especially within the Indonesian context.